THE INFLUENCE OF CHARACTERISTICS ON THE SPIRITUAL EDUCATION OF STUDENTS (TAMADDUN NURI JURNALI, 2024)
This article is about the causes of leprosy, the harms of leprosy and its treatment, and the ideas of Eastern thinkers in the work “Spiritual Education” by Shaykh Muhammad Sadiq Muhammad Yusuf, Mufti of the Islamic Religious Department of Central Asia and Kazakhstan, a member of the Inter-National Union - opinions about the role and importance of human qualities in spiritual education were studied.